Islam sebagai Agama Wasathiyah: Kajian Tafsir Maudhu’i tentang Moderasi Beragama - Samudra, Frio Efkaputra; Ayla, Indiana Fithra; Indra, Muhammad Dzaki; Muhyi, Asep Abdul (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study discusses the concept of religious moderation in the Qur’an using a thematic interpretation approach (maudhu’i). The aim is to understand how the Qur’an teaches a balanced, fair, and tolerant attitude in religion. Using qualitative descriptive-analytical methods and literature studies, this study refers to a number of interpretations such as Tafsir al-Miṣbāh, Fi Zilalil Qur’an, and Tafsir al-Azhar. The results of the study show that the value of moderation is reflected in the term wasathiyah which means middle and fair, as explained in QS. Al-Baqarah: 143 and other verses. This moderation is important to maintain harmony and prevent extreme views in religious and national life.